Lei de Acesso à Informação enquanto práticas de gestão da informação na Universidade Federal da Paraíba - Silva, Gabriella Gouveia da (2023)
Access to public information is a right granted by the Brazilian Federal Constitution of 1988, reinforced by the promulgation of the Law of Access Information (LAI) 12.527/2011. This right is one of the resources for society to control activities resulting from the administrative function of public agencies, allowing citizens to receive information from public administration through active transparency and requesting it through passive transparency. Information Management (IM) plays a crucial role in fulfilling these requirements by facilitating search and access to information through its treatment and prospecting and designing timely and appropriate responses for society. It becomes an indispensable requirement in organizations' strategic structures and elements, especially in Public Management, which must be qualified to make information available to users. Under this context, this work aims to analyze the process of Information Management in transparency, access, and use of information practices in the Physical Education Department of the Federal University of Paraíba, aiming to apply the LAP in current management practices. This study has descriptive qualitative and quantitative approaches. It was developed based on documentary and field research, applying a questionnaire in addition to the triangulation method. In the data analysis of the questionnaire responses, descriptive statistics are used on the data. The results are presented in tables, graphs, and figures for a better understanding. As a result, it was found that UFPB seeks to ensure access to information and transparency in the institution and fully or partially comply with the determinations of the LAI and the Active Transparency Guide. However, the role of IM is not effective, as this conformity does not reach all spheres of the institution. There is still much unfamiliarity by the studied academic community. It is pronounced by entrenched organizational culture regarding its rights and mechanisms to access available information. The results served as a basis for proposing the implementation of the chatbot LAIs, which would enable improvements in IM practices, access, and reach of public interest information at UFPB, starting with its Physical Education Department.